Evaluasi Gas Rumah Kaca(CH₄) dari Sektor Peternakan di Kelurahan Kalampangan - Muliana, Muliana; Azhari, Muh; Santoso, Achmad Imam (Media Ilmiah Teknik Lingkungan (MITL), 2021)
Air pollution is one of the environmental problems globally, such as the emission of methane gas (CH₄) which is produced from cow dung. Problems that are commonly encountered in cattle farming, such as livestock manure that is not managed properly, using the dry stack system, result in an increase in Greenhouse Gases (GHG). The yield of methane gas (CH₄) from the Ngudi Makmur livestock group, Kalampangan Village, is 0.00329 Gg CH₄/yr or 3,29 tons CH₄/yr from 70 cows in 2021. Methane gas (CH₄) level results from enteric fermentation by type cattle, Bali cattle produce the most methane gas and Brangus cattle produce the least methane gas.